Improving fifth-graders' learning outcomes of cube and cuboid nets using number head together cooperative learning - Vini Winda Puspita; Yarisda Ningsih (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2023)
This research is background by a low learning outcomes of students on learning cube and cuboid nets caused by learning that still uses conventional models and still teacher centered so that students are not yet active in the process learning. Type of research is classroom action research using quantitative and qualitative approaches. This research was conducted in the second semester of the 2021/2022 academic year. The research subjects were teachers as observers, researchers as practitioners, and 21th students consisting of 11 males and 10 females. The results showed an increase in the results: (1) RPP cycle I an average of 93.05% (A), cycle II 100% (A), (2) implementation in the teacher aspect of cycle I an average of 92.18% (A), and the second cycle 96.87% (A), (3) the implementation of the aspects of the students in the first cycle is 92.18% (A), the second cycle is 96.87% (A), and (4) The average student learning outcomes in the first cycle is 76.9% (B), the second cycle is 90.96% (A). The conclusion of the research is that using the numbered head together model increase student learning outcomes of cube and cuboid nets in elementary school in Padang.